Associations Between Intervertebral Disc Degeneration Grading Schemes and Measures of Disc Function. Issue 9 (20th May 2019) - Zehra, Uruj; Noel‐Barker, Natasha; Marshall, John; Adams, Michael A.; Dolan, Patricia
ABSTRACT: Disc degeneration is a major cause of spinal dysfunction and pain, but grading schemes concentrate on tissue changes rather than altered function. The aim of this study was to compare disc degeneration grading systems with each other, and with biomechanical measures of disc function. Sixty‐six motion segments (T8–9 to L5–S1) were dissected from cadavers aged 48–98 years. Disc function was assessed by measuring nucleus pressure (IDP) and maximum stresses in the annulus under 1 kN of compression. Detailed "scores" of disc degeneration were based on independent radiographic, macroscopic, and microscopic evaluations. For each evaluation, scores were used to assign a degeneration "grade" (I–IV), and functional measures were then correlated with degeneration scores and grades. Results showed that all measures were reliable (intraclass correlation coefficients: 0.82–0.99). Macroscopic and microscopic assessments were highly correlated with each other ( r : 0.57–0.89, p  < 0.001) but only weakly correlated with radiographic features. The overall macroscopic and microscopic scores of degeneration increased significantly with age and at lower spinal levels, although the influence of age was less marked in the case of the microscopic scores. IDP decreased with age and at lower spinal levels, but annulus stresses were more variable. Importantly, IDP and annulus stresses decreased consistently with all measures of disc degeneration, and these associations remained strong after controlling for age, gender, and spinal level. We conclude that radiographic and tissue‐based assessments of disc degeneration are consistent with each other, and are more closely related to mechanical (dys)function than to age or spinal level. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:1946–1955, 2019